Fretting fatigue total life assessment including wear and a varying critical distance. (March 2022) - Pinto, A.L.; Talemi, R.; Araújo, J.A.
Abstract: This work presents methodologies for fretting fatigue life assessment that include the wear effect and crack propagation. The multiaxial fatigue parameter SWT and the theory of critical distance TCD were used to compute the damage, the node-displacement algorithm was applied to account wear, and the XFEM method to modeling the crack. Available fretting fatigue experiments conducted on a cylinder-on-flat contact configuration made of Al 2024-T351 alloy were used to evaluate the methodology. To apply the approach in the medium-cycle fatigue regime, the critical distance is assumed to depend on the fatigue life. All fatigue life estimates using TCD as a function of life were within factor-of-two boundaries. Highlights: Fretting fatigue in partial slip regime life assessment is carried out for Al2024-T3. The numerical method proposed including wear effects and crack propagation life. A new method based on the critical plane to predict the crack propagation angle. The methodology proposed obtained more accurate predictions than simple methods. The energy dissipated can be used to know when computing wear or crack propagation.